2010
DOI: 10.1007/s11661-010-0289-0
|View full text |Cite
|
Sign up to set email alerts
|

On Peritectic Reactions and Transformations in Low-Alloy Steels

Abstract: Differential thermal analysis (DTA) experiments on low-alloy steels with varying C, Si, Cr, and Mo contents indicated an increase in the difference between the liquidus and peritectic temperatures during solidification with the decrease in C and increase in Mo contents. In a number of the quenched samples, massive transformations of ferrite to austenite were observed. Electron microprobe analysis of the diffusion across a massive transformation front, along with the high growth rates estimated, gives strong re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The vertical red arrows show the growth direction of the samples, the positions of the solid/liquid interface and the peritectic interface are indicated by the small blue arrows. The dark/grey phases represent primary Ni 3 Sn 2 /peritectic Ni 3 Sn 4 phases, respectively; and the remaining white is the eutectic 4 8 9 . It is worth noting that four different zones can be observed in the samples after isothermal annealing: the complete liquid zone, the (Ni 3 Sn 2 + liquid) mushy zone, the (Ni 3 Sn 2 + Ni 3 Sn 4 + liquid) mushy zone, below T E is the complete solid region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical red arrows show the growth direction of the samples, the positions of the solid/liquid interface and the peritectic interface are indicated by the small blue arrows. The dark/grey phases represent primary Ni 3 Sn 2 /peritectic Ni 3 Sn 4 phases, respectively; and the remaining white is the eutectic 4 8 9 . It is worth noting that four different zones can be observed in the samples after isothermal annealing: the complete liquid zone, the (Ni 3 Sn 2 + liquid) mushy zone, the (Ni 3 Sn 2 + Ni 3 Sn 4 + liquid) mushy zone, below T E is the complete solid region.…”
Section: Resultsmentioning
confidence: 99%
“…Besides peritectic transformation, the peritectic β phase can also be foremd through precipitation from the liquid phase L. The driving force of this solid-state transformation is the diffusion driven by the compositional difference across β phase. Here and are the concentrations of peritectic β phase in equilibrium with the liquid and primary α phase, respectively 1 2 3 4 . Researches in isothermal condition 5 6 or slow cooling solidification 2 4 7 8 9 , especially in Fe-C 4 7 8 and Fe-Ni 9 peritectic alloys have shown that peritectic transformation could not be simply ignored.…”
mentioning
confidence: 99%
“…3. Nassar et al 7) argued that the shape and the velocity of the γ platelet are determined by the high surface tension at the γ/δ interface, which is a result of the elastic strain between γ and δ. This however could not be confirmed by Ohno et al, 8) who investigated the effect of the interfacial energy on the rate of the peritectic reaction by using phase-field simulation.…”
Section: Peritectic Reactionmentioning
confidence: 99%
“…A new mechanism for the peritectic reaction was proposed by Phelan et al, 6) who suggested that the peritectic reaction is controlled by the rate of dissipation of heat of transformation that is released by the growing γ phase. In a different approach, Nassar et al 7) argued that the shape of the γ phase near the triple point L/γ/δ during the peritectic reaction is determined by the high surface tension at the γ/δ interface, which is a result of the elastic strain between γ and δ. They further argued that this strain causes an increase in Gibbs free energy, leading to an undercooling below the equilibrium peritectic temperature, thus explaining the high observed reaction velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at high cooling rates, the transformation occurred very rapidly without any diffusion of the alloying elements into the interior of the ferrite. Nassar and Fredriksson [15] performed many DTA experiments on low-alloy steels and observed a massive transformation of d to c, which they attributed to stress relief relaxation, since such a transformation rate cannot be explained by a diffusion-driven transformation.…”
Section: Introductionmentioning
confidence: 99%